Chronic fluoride exposure induces neuronal apoptosis and impairs neurogenesis and synaptic plasticity: Role of GSK-3β/β-catenin pathway. (January 2019) - Jiang, Pei; Li, Gongying; Zhou, Xueyuan; Wang, Changshui; Qiao, Yi; Liao, Dehua; Shi, Dongmei
Abstract: Fluoride is becoming an ineluctable environmental pollutant and its longterm exposure would cause fluorosis and irreversible brain damage, but the molecular mechanisms remain far from fully understood. In the present study, we firstly evaluated the glycogen synthase kinase 3β (GSK-3β)/β-catenin pathway in the hippocampus of rats exposed to fluoride, given the well-established role of GSK-3β/β-catenin pathway in neuronal death and survival. Our data showed that sustained exposure to 50 mg/L and 100 mg/L NaF in drinking water dose-dependently induced neuronal loss and apoptosis in rat hippocampus. Neurogenesis was also weakened by fluoride administration in the hippocampal dentate gyrus region. Additionally, the synaptic markers, synaptophysin (SYP) and post-synaptic density 95 (PSD95) protein levels, were decreased by 100 mg/L NaF treatment, whereas 50 mg/L NaF only reduced SYP expression, indicating a compromised synaptic function. We further demonstrated that NaF, especially the higher dose, induced GSK-3β activity, with decreased inactive phosphorylated GSK-3β levels and increased GSK-3β, the active form of the kinase. Correspondingly, downstream β-catenin signaling was undermined by NaF treatment as evidenced by the fact that both two doses of NaF decreased nucleus β-catenin status and the higher dose of NaF also reduced cytoplasmic β-catenin protein expression. Taken together, the present study firstly showed the aberrant changes of GSK-3β/β-catenin signaling in the fluoride-exposed brain, highlighting the involvement of GSK-3β/β-catenin signaling in the fluoride-induced neurotoxicity. Highlights: Fluoride dose-dependently impaired neurogenesis and synaptic function. Fluoride exposure induced hippocampal neuronal loss and apoptosis. Fluoride exposure compromised GSK-3β/β-catenin signaling. Fluoride decreased β-catenin downstream target genes, cyclin D1 and c-myc.